A longitudinal molecular surveillance of genetic heterogeneity of Orientia tsutsugamushi in humans, reservoir animals, and vectors in Puducherry, India - Sihag, Krishan Kumar; Arif, Waseema; Srirama, Srikanth; Chandrasekaran, Anand Kumar; Raveendran, Vinod; Chandrakumar, Asayas Bosco; Kasirajan, Anand; Thavaraj, Sivagamy Alias Punitha; Srinivasan, Lakshmy; Choolayil, Anoop C.; Ashokkumar, Mathivanan; Ramasamy, Amala; et al. (Frontiers in Microbiology, 2025)
BackgroundScrub typhus (ST), is a vector borne zoonotic disease, transmitted by the larva of the trombiculid mites. The enzootic cycle of the pathogen involves rodents/shrews as the animal reservoirs and humans are the accidental dead-end host. A transposon-like activity in its major antigen 56 kDa, has led to the evolution of several serotypes/strains, and more than 40 serotypes are reported globally. Puducherry, India, is endemic to scrub, but limited data exist on local serotype distribution across hosts and vectors.MethodologyA longitudinal molecular surveillance was conducted in Puducherry to investigate the genetic diversity of Orientia tsutsugamushi among humans, animal reservoirs, and vectors. Samples from febrile patients, trapped rodents/shrews, and their infesting mites were screened using real-time and nested PCR. Serotype analysis was performed by partial amplification and sequencing of the 56 kDa gene, followed by phylogenetic, pairwise genetic distance and amino acid analysis.ResultST infection was detected in 4.37% (95% CI: 3.05–5.71%) of human, 11.52% (95% CI: 8.6–14.4%) of rodent/shrew, and 2.36% (95% CI: 0.95–4.87%) of mite samples. Karp-like (51.72%) and Gilliam-like (41.38%) strains were predominant in both humans and animal hosts, with pairwise genetic distance (<0.1) and amino acid identity (>85%) analysis revealing a close relationship between the strains identified across the region. Notably, the only mite pool that tested positive for the 56 kDa gene, along with a shrew, was identified to belong to the TA678-like serotype (6.90%), which has not been previously reported from Puducherry.ConclusionThis study provides molecular evidence of the enzootic maintenance and active human transmission of O. tsutsugamushi in Puducherry, with multiple co-circulating serotypes. The first detection of the TA678-like strain in the region suggests the possible introduction of new strains and underscores the need to monitor for strain-specific clinical manifestations in future studies.